Strategic Internal Communication in Organizational Change: A Narrative Review of Practices and Barriers - Adnan, Iis Zilfah; Suratmoko, Bayu (Communica : Journal of Communication, 2024)
This narrative review explores the strategic role of internal communication in driving successful organizational change. The review aims to identify effective communication techniques, assess employee engagement dynamics, evaluate the integration of digital tools, and examine cross-cultural and sectoral differences. A structured review methodology was employed using literature from Scopus, Web of Science, JSTOR, and Google Scholar. Keywords included "internal communication," "organizational change," "strategic messaging," and "employee engagement." Studies were selected based on relevance, methodological rigor, and publication within the last decade. The findings reveal that two-way communication, credible messaging, and digital platforms such as Slack and Microsoft Teams significantly enhance transparency and employee commitment. Empirical evidence highlights trust as a key mediator in fostering engagement, with participatory communication models proving most effective. Comparative analysis shows that communication strategies vary widely across cultures and sectors, influenced by organizational hierarchies and societal values. Systemic barriers such as leadership misalignment and emotional resistance remain challenges to implementation. This review concludes that effective internal communication is essential for reducing resistance and promoting sustainable transformation. Policies encouraging leader training, technological integration, and inclusive culture development are recommended. Future studies should address digital innovation and longitudinal impacts to enrich the literature and practice of change management.